2005
DOI: 10.1021/np049698a
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrochalcones from the Leaves of Pieris japonica

Abstract: Six new dihydrochalcones, 3-hydroxyasebotin (5), asebogenin 2'-O-beta-D-ribohexo-3-ulopyranoside (6), 2' '-acetylasebotin (7), 3',4,5'-trihydroxy-4'-methoxydihydrochalcone 3',5'-di-O-beta-D-glucopyranoside (8), and pierotins A (9) and B (10), along with four known dihydrochalcones, phloretin (1), phlorizin (2), asebogenin (3), and asebotin (4), were isolated from the leaves of Pieris japonica. Their structures were elucidated on the basis of spectroscopic analysis including HMQC, HMBC, NOESY, and X-ray crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 13 publications
1
34
0
1
Order By: Relevance
“…The coupling constants J 1′,2′ ) 7.9 Hz and J 1′′,2′′ ) 1.3 Hz indicated a glycosidic linkage of the glucopyranosyl sugar moiety and an R glycosidic linkage of the 4′′-Oacetylrhamnopyranosyl residue. 16,19 Acid hydrolysis followed by derivatization with L-cysteine methyl ester hydrochloride confirmed the absolute configurations of the sugar moieties as D-glucose and L-rhamnose as determined by GC analysis. Thus The HSQC spectrum also exhibited one anomeric signal (δ C 100.1, δ H 4.90), revealing the presence of a sugar moiety at C-11 (δ 68.6) as determined by analysis of the HMBC spectrum.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The coupling constants J 1′,2′ ) 7.9 Hz and J 1′′,2′′ ) 1.3 Hz indicated a glycosidic linkage of the glucopyranosyl sugar moiety and an R glycosidic linkage of the 4′′-Oacetylrhamnopyranosyl residue. 16,19 Acid hydrolysis followed by derivatization with L-cysteine methyl ester hydrochloride confirmed the absolute configurations of the sugar moieties as D-glucose and L-rhamnose as determined by GC analysis. Thus The HSQC spectrum also exhibited one anomeric signal (δ C 100.1, δ H 4.90), revealing the presence of a sugar moiety at C-11 (δ 68.6) as determined by analysis of the HMBC spectrum.…”
mentioning
confidence: 80%
“…The HRFABMS spectrum displayed a quasimolecular ion at m/z 1 H and 13 C NMR Data for Compounds 4-6 (C 5 D 5 N) 16 . Thus, compounds 4 and 3 were isomers.…”
mentioning
confidence: 99%
“…Likewise, dihydrochalcone asebogenin (27), which is found in several plants, including Piper aduncum, and used as a condiment and for cocoa flavoring, downregulated the proliferation of murine B cells [180].…”
Section: Effect Of Chalcones On Tumor Progressionmentioning
confidence: 99%
“…Comparison of 1D-NMR data suggested that CH 2 (15) in the latter compound was replaced by an O-bearing CH group, with an additional OH group at C(15) in 4. This deduction was confirmed by HMBCs of HÀC (15) with C(7), C(8), C(13), C (14), and Me (17), and of HÀC (9), HÀC (14), and Me (17) The known compounds were determined as pierisoid A [8], pierisoid B [8], secorhodomollolide D [7], pierisformosin B [4], asebotoxin IV [24], asebotoxin V [24], asebotoxin VIII [25], grayanotoxin-I [26], grayanotoxin-III [27], 5,6-acetonylgrayanotoxin-I [28], grayanotoxin XXII [16], oleanolic acid [29], ursolic acid [30], bsitosterol [31], bayogenin [32], arjunolic acid [33], (2S,3R)-ent-catechin [34], 2',4-dihydroxy-4'-methoxy-6'-O-b-glucopyranoside dihydrochalcone [35], asebotin [36], bis-8,8'-catechinylmethane [37] [41], and 2,6-dimethoxy-4-hydroxyphenol 1-O-b-d-glucopyranoside [42] by comparison of their spectral data with literature values.…”
mentioning
confidence: 99%